Crimean-Congo Hemorrhagic Fever (CCHF) in Turkey: A zoonosis which can cause nosocomial infection: Invited commentary - (:unkn) unknown (Turkiye Klinikleri, 2008)
[No abstract available]
Keywords: Crimean-Congo Hemorrhagic Fever; Nosocomial; Tick; Zoonosis